Sclerostin is an independent risk factor for all-cause mortality in kidney transplant recipients - Zeng, Shufei; Slowinski, Torsten; Pommer, Wolfgang; Hasan, Ahmed A.; Gaballa, Mohamed Mahmoud Salem Ahmed; Lu, YongPing; Krämer, Bernhard; Hocher, Berthold (Clinical and experimental nephrology, 2020)
Sclerostin is a hormone contributing to the bone-vascular wall cross talk and has been implicated in cardiovascular events and mortality in patients with chronic kidney disease (CKD). We analyzed the relationship between sclerostin and mortality in renal transplant recipients.